Judy Moody The Doctor Is In! [Doktorka Dada Nálada anglicky] / Book 5. - McDonald, Megan 1959- (Walker Books Ltd, 2019)
Judy Moody has got the Moody Monday blues - until she finds out that her class's new project is on the amazing human body. That means skeletons, skulls, a hospital trip, lots of medical jokes and double trouble when Judy's friends trick her into thinking the class guinea pig has been cloned! But when Judy catches the mumps off her younger "bother", Stink, her friends make it up to her by coming to visit.